Low genetic diversity suggests a single introduction and recent spread of tomato chlorosis virus in Brazil - Barbosa, Júlio C.; Rezende, Jorge A. M.; Filho, Armando B. (Wiley, 2013)
By comparing the partial nucleotide sequences of the heat shock protein HSP70 homologue gene, we assessed the genetic diversity of Brazilian tomato isolates of Tomato chlorosis virus (ToCV), as well as their relationship with other ToCV isolates found worldwide. The Brazilian ToCV isolates shared 99.9-100% nucleotide identity, which indicates low genetic diversity. Brazilian ToCV isolates showed a closer evolutionary relationship to those from Mediterranean countries. Based on these results, the origin of Brazilian ToCV isolates and the possible number of introductions of the virus into Brazil are discussed. © 2013 Blackwell Verlag GmbH.
Keywords: Brazil; Crinivirus; Molecular epidemiology; Solanum lycopersicum; Tomato chlorosis virus